2017
DOI: 10.1016/j.devcel.2017.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Bleb Expansion in Migrating Cells Depends on Supply of Membrane from Cell Surface Invaginations

Abstract: Cell migration is essential for morphogenesis, for organ formation and homeostasis, with relevance for clinical conditions. The migration of primordial germ cells (PGCs) is a useful model to study this process in the context of the developing embryo. Zebrafish PGC migration depends on the formation of cellular protrusions in form of blebs, a type of protrusion found in various cell types. Here we report on the mechanisms allowing the inflation of the membrane during bleb formation. We show that the rapid expan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 68 publications
6
44
0
Order By: Relevance
“…Other cell types that migrate using blebs, such as zebrafish primordial germ cells (PGCs), rely on Rac activity to support bleb growth (Kardash et al, 2010). Bleb-based motility in PGCs also relies on Cdc42-dependent 'wrinkling' of the plasma membrane to create membrane reservoirs that can be released as blebs form and expand (Goudarzi et al, 2017). Since the Cdc42/WASP axis supports neutrophil polarity (Fritz-Laylin et al, 2017;Yang et al, 2016), it would be interesting to test whether this pathway contributes to membrane wrinkling in neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…Other cell types that migrate using blebs, such as zebrafish primordial germ cells (PGCs), rely on Rac activity to support bleb growth (Kardash et al, 2010). Bleb-based motility in PGCs also relies on Cdc42-dependent 'wrinkling' of the plasma membrane to create membrane reservoirs that can be released as blebs form and expand (Goudarzi et al, 2017). Since the Cdc42/WASP axis supports neutrophil polarity (Fritz-Laylin et al, 2017;Yang et al, 2016), it would be interesting to test whether this pathway contributes to membrane wrinkling in neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…PGC migration is regulated by transmembrane receptors that receive external chemoattractant signals, which are then translated to cytoskeletal change by effector molecules such as phospholipids and small GTPases ( Richardson and Lehmann, 2010 ; Barton et al, 2016 ). A recent study indicated that expression of a dominant-negative form of small GTPase Cdc42 in the PGC led to round cell morphology, decreased formation of the membrane invaginations, and reduced blebbing ( Goudarzi et al, 2017 ). However, the molecular mechanism underlying Cdc42 expression and regulation in PGCs was remained unclear in zebrafish.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence indicate that EVs generated by highly aggressive cancer cells are capable of promoting tumor growth [47][48][49]. We showed in Fig.…”
Section: Discussionmentioning
confidence: 61%
“…One possible explanation for this is that membrane sources for blebbing are diminished upon Rab11 inhibition. Bleb inflation is the result of unfolding of stored membrane, which could originate from fusion of Rab11 vesicles with plasma membrane [46,47]. Alternatively, Rab11 inhibition may prevent cytoplasmic flow from pushing the membrane outwards.…”
Section: Discussionmentioning
confidence: 99%